PENGARUH PEMBERIAN DAUN UBI JALAR DENGAN DOSIS YANG BERBEDA TERHADAP KELULUS HIDUPAN BENIH IKAN MAS (CYPRINUS CARPIO L.) DALAM PENGANGKUTAN - administrator admin; Dian Anggraini (Selodang Mayang: Jurnal Ilmiah Badan Perencanaan Pembangunan Daerah Kabupaten Indragiri Hilir, 2016)
This research has been conducted for on 1 week (5th February – 12February 2015), whichplaced in UPTBAT Rumbai from Pekanbaru to Tembilahan. The goal of this research is toknow about how the influence of given the potato sweet’s leaf with different dose towardsurvival rate of goldfish seed (Cyprinus carpio L) in transportation. The experiment methodeis applied with 4 treatments and 3 times. According to the result of each treatment can beseen that A (100 gram) is 99%, treatment B (120 gram) 97%, treatment C (140 gram)92,5%, and control 90%. From this research, can be conclued that the best survival rate thegoldfish in transportation is in treatment A (100 gram).